FLOW INJECTION POTENTIOMETRIC ANALYSIS OF ASPARTIC ACID, GLUTAMIC ACID AND ASCORBIC ACID USING PLATINUM ELECTRODES - Yeni Maulidah Muflihah; Siswoyo Siswoyo; Tanti Haryati; Kiki Puji Setianingrum (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2012)
The presence of weak acids in solution can be detected using a potentiometric detector. Platinum was used as a working electrode and Ag/AgCl as a reference electrode. Ascorbic, glutamic and aspartic acid were detected by a platinum electrode in a flow potentiometric system. The influence of pH, flow rate and concentration of phosphate buffers asa a carrier were studied and showed an optimum pH for the detection of ascorbic and glutamic acid at pH 6,5 and pH 7,0 for aspartic acid. Phosphate buffer concentration optimum at 1x10-4M and flow rate of 1,00 mL/min. Linear range for ascorbic and glutamic acid at 2,5 x10-4M to 5x10-2M, with a regression coefficient of 0,974 and 0,958, while for aspartic acid 5x10-4M to 5x10-2M with a regression coefficient 0,911. Detection limit for ascorbic and glutamic acids were 5x10-4M and 1x10-3M for aspartic acid. Sensor reproducibility obtained from variation coefficient (Kv). Variation coeffiecient (Kv) of ascorbic acids 1,32-1,69%, glutamic acids 0,69- 1,57% and aspartic acid 0,54- 1,29%.